1988
DOI: 10.1111/j.1365-2788.1988.tb01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and Alzheimer's disease in subjects with Down's syndrome

Abstract: ABSTRACT. People with Down's syndrome (DS) are at high risk of developing Alzheimer's disease (AD). The gene coding for Superoxide dismutase‐/ on chromosome 21 resulting in excess activity of the enzyme with consequent risk of oxidative damage might account for the premature ageing. Vitamin E protects against such damage. Plasma vitamin E levels measured in 12 DS subjects with AD (8.19·0.77 μg/ml) were lower (P<0.05) than in 12 DS controls (9.43·1.57 μg/ml). It is suggested that there may be an interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The levels of glutathione are decreased in these individuals [38][39][40] and increased oxidized glutathione/glutathione ratio has been found in fibroblasts from DS fetuses [36]. Additionally, lower blood and/or plasma levels of other antioxidant molecules such as vitamin E, vitamin C, selenium, and zinc have been found in children and adult DS individuals [38,[41][42][43]. Furthermore, fetal DS brains show reduced levels of taurine in the frontal cortex [44].…”
Section: Mechanisms Of Os Involved In Dsmentioning
confidence: 99%
“…The levels of glutathione are decreased in these individuals [38][39][40] and increased oxidized glutathione/glutathione ratio has been found in fibroblasts from DS fetuses [36]. Additionally, lower blood and/or plasma levels of other antioxidant molecules such as vitamin E, vitamin C, selenium, and zinc have been found in children and adult DS individuals [38,[41][42][43]. Furthermore, fetal DS brains show reduced levels of taurine in the frontal cortex [44].…”
Section: Mechanisms Of Os Involved In Dsmentioning
confidence: 99%
“…Studies have shown that vitamin E deficiency impairs cognitive performance in mice subjected to oxidative stress [ 2 ]. Meanwhile, one study found that Down syndrome (DS) children have significantly less vitamin E levels than normal children [ 3 ]; while another study showed that DS patients with dementia have lower plasma levels of vitamin E than controls without DS [ 4 ]. These results suggest that intake of essential nutrients such as folate, vitamin B6, vitamin E, selenium, α-lipoic acid might be important in preventing cognitive deterioration in DS and Alzheimer disease (AD) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%